Pediatric Paroxysmal Exercise-Induced Neurological Symptoms: Clinical Spectrum and Diagnostic Algorithm - Danti, Federica Rachele; Invernizzi, Federica; Moroni, Isabella; Garavaglia, Barbara; Nardocci, Nardo; Zorzi, Giovanna (Frontiers in Neurology, 2021)
The Paroxysmal exercise-induced neurological symptoms (PENS) encompass a wide spectrum of clinical phenomena commonly presenting during childhood and characteristically elicited by physical exercise. Interestingly few shared pathogenetic mechanisms could be identified. Beyond the well-known entity of paroxysmal exercise-induced dyskinesia, PENS could be part of more complex phenotypes including neuromuscular, neurodegenerative and neurometabolic disease, epilepsies and psychogenetic disorders. The wide and partially overlapping phenotype and the genetic heterogeneity make the differential diagnosis frequently difficult and delayed; however, since some of these disorders may be treatable, a prompt diagnosis is mandatory. Therefore, an accurate characterization of these symptoms is pivotal for orienting more targeted biochemical, radiological, neurophysiological and genetic investigations and finally treatment. In this article, we review the clinical, genetic, pathophysiologic and therapeutic landscape of paroxysmal exercise induced neurological symptoms, focusing on phenomenology and differential diagnosis.